Case Management and Care Coordination: Supporting Children and Families to Optimal Outcomes - Treadwell, J (Springer, 2015)
New collaborative models of health care service delivery are contributing to quality and cost improvements, especially in treating children and families. At the same time, deficits in communication between systems sharing patients can not only lead to confusion and waste, but also to increased risk of harm.